Efetividade do uso de laser sobre a parestesia de nervos trigeminais decorrente de traumas cirurgicamente induzidos : revisão sistemática - Bobrowski, Ângelo Niemczewski (2021)
The objective of this work was to answer the question: is laser therapy on trigeminal nerve paresthesia, resulting from different types of surgical trauma, is it or not effective for its reversal? A systematic review of the literature was performed using the Databases: PubMed, Scopus, Cochrane Library, Web of Science, Virtual Health Library and Embase, resulting in 68 articles. Of these, twenty-one articles were included in the final review after a complete reading of the papers. Out of a total of 21 articles included in the final review, 20 articles totaled 303 patients who received low-level laser therapy on at least one side of the face (right or left), after having suffered surgical trauma that caused the paresthesia and responded to treatment positively in recovery or, at least, in accelerating the recovery of sensorineural deficit – partially or total. Only one study failed to provide sufficient evidence to conclude that there is a difference in sensorineural improvement. The use of low-level therapy was effective in sensorineural recovery or in accelerating the recovery of sensorineural deficit, when applied to the branches of the trigeminal nerve, resulting from surgically induced traumas.